Application of artificial neural network in assessment of mechanization degree of modern agriculture yard - ZHENG Jin-tu; LI Li; GU Cheng-gang (浙江大学学报. 农业与生命科学版, 2000)
Applies artificial neural network to the assessment of mechanization degree of modem agriculture, introduces assessment theory based on artificial neural network and builds assessment model of mechanization degree of agriculture yard. It is proved that this method has certain credibility by using example.